KONSELING BERBASIS TEXT BASED COUNSELING DALAM LAYANAN BIMBINGAN DAN KONSELING OLEH GURU BK DI SEKOLAH MENENGAH PERTAMA - Dwika Sukma Dewi; Herdi Herdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study aims to describe text-based counseling by counseling teachers in the era of society 5.0. This study surveyed data using the Google form and used a quantitative descriptive approach. Respondents to this study were counseling teachers who served in junior high schools in Bandung. The number of samples in the study was 32 counseling teachers who filled out the Google form and 6 counseling teachers who were willing to carry out the interview process. The results of the study show that counseling teachers prefer text-based online counseling media, with the WhatsApp application.